Transposon Mutagenesis of Gene Involved in Limonin Degradation in Pseudomonas Putida - Sharma, Mirnalini (My University, 2007)
Microorganisms are metabolically versatile as a function of wide range of catalyzing enzymes and can degrade variety of complex organic and inorganic compounds. Some of the predominant microorganisms that possess such capabilities are Pseudomonas, Arthrobacter, Rhodococcus, Bacillus, Aspergillus, and E.coli etc. Among these Pseudomonas is ubiquitous and possesses diverse metabolic capability for utilizing different complex aliphatic and aromatic compounds. Limonin, a phytochemical belongs to the class of limonoids, which are one of the bitter principles in citrus juices. It is a highly oxygenated triterpenoid compound, which comprises of a furan ring and an epoxide group. Limonin is chemically related to triterpene derivatives found in Rutaceae and Malvacae families and accounts for most of the delayed bitterness in citrus fruit juices. This delayed bitterness due to limonin is a serious economic problem of citrus juice industry worldwide and attempts are being made to solve the problem by either preventing limonin formation or removal after it is formed. But the existing methods have severe economic and technical limitations since they impair the quality and stability of the juice by affecting the components other than limonin. The successful use of microorganisms depends on development of better understanding of molecular mechanisms adapted to degrade limonin. A few microorganisms that have been studied to degrade limonin include Arthrobacter globiformis, Pseudomonas 321-18, Corynebacterium facians, Rhodococcus sp. However no molecular characterization at genetic level of any microorganism has been done with respect to limonin degradation or metabolism. One of the putative microorganisms in response to limonin metabolism is Pseudomonas due to its diverse metabolic capabilities to degrade large variety of substrates as carbon source. The ability to utilize limonin is characterized in Pseudomonas putida, by virtue of its metabolism. It is already well established that Pseudomonas putida is a nutritional opportunist par excellence and paradigm of metabolically versatile microorganism. An arsenal degradative function presumably reflects its existence spectrum of housekeeping catabolic pathways and enzymes. However so far no known strains of P.putida has been studied from the perspective of limonin degradation.
Keywords: Pseudomonas Putida; Ransposon Mutagenesis of Gene; Corynebacterium Facians; Limonin